Shuttle MMOD Impact Database. (2015) - Hyde, J.; Christiansen, E.; Lear, D.
Abstract: The Shuttle Hypervelocity Impact Database documents damage features on each Orbiter from micrometeoroids (MM) and orbital debris (OD). Data is divided into tables for crew module windows, payload bay door radiators and thermal protection systems along with other miscellaneous regions. The database contains nearly 3000 records, with each providing impact feature dimensions, location on the vehicle and relevant mission information. Additional detail on the type and size of particle that produced the damage site is provided when sampling data and definitive spectroscopic analysis results are available. Relationships assumed when converting from observed feature sizes in different shuttle materials to particle sizes will be presented.